Strategi Mitigasi Risiko Fraud Pengadaan Pemerintah: Mitigation Strategies Against the Fraud Risk of Government Procurement - kamal, Mustofa (Puslatbang KHAN, 2023)
Fraud in the procurement sector is still high and there are 58 risks of procurement fraud. Meanwhile, risk assessment and handling mandates have been in place. However, there is no research on handling the risk of fraud. This study aims to reveal an overview of control development in the context of handling procurement fraud risks according to the results of the evaluation and the level of PBJP fraud risk. Qualitative research is carried out through literature studies, normative studies and prospective studies related to handling the risk of procurement fraud with the highest level in the form of procurement planning not in accordance with riel needs. The results showed that the design of controlling the risk of fraud